The effect of microbiome therapy on COVID-19-induced gut dysbiosis: A narrative and systematic review - Mahmoud Yousef (9900837) (2024)
Aims Emerging evidence highlights the role of COVID-19 in instigating gut dysbiosis, with repercussions on disease severity and bidirectional gut-organ communication involving the lung, heart, brain, and liver. This study aims to evaluate the efficacy of probiotics, prebiotics, synbiotics, and fecal microbiota transplantation (FMT) in addressing gut dysbiosis associated with COVID-19, as well as their impact on related disease severity and clinical outcomes. Materials and methods We systematically review 27 studies exploring the efficacy of different microbiome-modulating therapies: probiotics, prebiotics, synbiotics, and fecal microbiota transplantation as potential interventions for COVID-19. Key findings The probiotics and synbiotics investigated encompassed a spectrum of eight bacterial and fungal genera, namely Lactobacillus, Bifidobacterium, Streptococcus, Enterococcus, Pediococcus, Bacillus, Saccharomyces, and Kluyveromyces. Noteworthy prebiotics employed in these studies included chestnut tannin, galactooligosaccharides, fructooligosaccharides, xylooligosaccharide, and resistant dextrin. The majority of the investigated biotics exhibited positive effects on COVID-19 patients, manifesting in symptom alleviation, inflammation reduction, and notable decreases in mortality rates. Five studies reported death rates, showing an average mortality ranging from 0 % to 11 % in the intervention groups, as compared to 3 % to 30 % in the control groups. Specifically, probiotics, prebiotics, and synbiotics demonstrated efficacy in diminishing the duration and severity of symptoms while significantly accelerating viral and symptomatic remission. FMT emerged as a particularly effective strategy, successfully restoring gut microbiota and ameliorating gastrointestinal disorders. Significance The insights gleaned from this review significantly contribute to our broader comprehension of the therapeutic potential of biotics in addressing COVID-19-related gut dysbiosis and mitigating secondary multi-organ complications. Graphical abstract COVID-19 induces gut dysbiosis and inflammation across multiple organ systems. Further, bidirectional communication between the gastrointestinal tract and vital organs like the lung, heart, brain, and liver can exacerbate the disease severity and cause further inflammation and dysbiosis. This systematic review investigated the efficacy of interventions such as probiotics, prebiotics, synbiotics, and fecal microbiota transplantation (FMT) in COVID-19 management, and this revealed promising outcomes. These interventions reduced mortality rates, decreased hospital stays, improved oxygen saturation levels, alleviated gastrointestinal symptoms, enhanced immune response, and improved cognition. Other Information Published in: Life Sciences License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.lfs.2024.122535